Analisis Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Kiru-Kiru, Kabupaten Barru: Analysis of the Development of Micro, Small, and Medium Enterprises (UMKM) in Kiru-Kiru Urban Village, Barru Regency - Putri, Deasy Soraya A Aminartha; Syah, Firman; Amaliah, Izzatul; Febrianti, Suci (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Micro, Small, and Medium Enterprises (UMKM) play a strategic role in driving local economic growth and improving community welfare. This study aims to analyze the conditions, challenges, and development strategies of UMKM in Kiru-Kiru Village, Soppeng Riaja District, Barru Regency in 2025. This research employs a qualitative descriptive approach supported by quantitative data. Data collection techniques were conducted through observation, interviews, and distributing questionnaires to UMKM actors. The obtained data were analyzed descriptively and thematically. The results indicate that UMKM in Kiru-Kiru Village are dominated by family-based micro-enterprises with limited production capacity and high dependency on the local market. The main obstacles faced include capital limitations and lack of access to formal financing, low managerial skills, and minimal utilization of digital marketing. Furthermore, guidance from the government and local institutions remains incidental and has not been followed by continuous mentoring. Nevertheless, UMKM in Kiru-Kiru Village possess significant development potential through human resource capacity building, the utilization of digital technology, and institutional strengthening of business groups or UMKM clusters.